1999
DOI: 10.1094/cchem.1999.76.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Temperature on Physicochemical Properties of Starch Isolated from Pasta

Abstract: Cereal Chem. 76(4):541-547Semolina from four durum wheat genotypes (cvs. Ben, Munich, Rugby, and Vic) were processed into spaghetti that was dried by low (LT), high (HT), and ultrahigh (UHT) temperature drying cycles. Starch was isolated from dried pasta and unprocessed wheat and semolina references. Pasta-drying cycles had no significant effect on the amylose content of starches. Significant increases in enzyme-resistant starch were observed in HT-and UHT-dried pasta (2.27 and 2.51%, respectively) compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 16 publications
6
55
0
2
Order By: Relevance
“…This finding is in accordance with the report of Yue et al, 50 who did not find any difference in amylose content of semolina and dried pasta. Conversely, we observed a very high and significant increase of amylose content after cooking.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the report of Yue et al, 50 who did not find any difference in amylose content of semolina and dried pasta. Conversely, we observed a very high and significant increase of amylose content after cooking.…”
Section: Discussionsupporting
confidence: 93%
“…• C); high temperature (70 • C); and THT (90 • C) using the drying cycles described by Yue et al 17 All three drying cycles began at 85% and ended at 50% relative humidity.…”
Section: Extrusionmentioning
confidence: 99%
“…The CPV value for treated pasta varied between 11459 cP (1 bar/25 sec) and 10560 cP (3.9 bar/25 sec) while it was 11581 cP for the raw pasta. Yue et al, (1999) suggested that the lower final viscosities of HT-dried pasta samples could be partially explained by greater amylose-lipid complex formation that may have restricted recrystallization of amylose during cooling. Güler et al, (2002) confirmed these observations by X-ray diffraction.…”
Section: Rva Parametersmentioning
confidence: 99%